Application of portfolio assessment and management tools in the furniture segment: a case study - Antoniol, Vinicius Costa; Fonseca, Mariana Paes da; Marcomini, Raphael Fortes (Brazilian Journal of Production Engineering, 2023)
Portfolio management is of fundamental importance for the product development process, as it seeks to improvedecision-making and resource optimization, which is of paramount importance for any organization. The literature reports several tools to operationalize portfolio management, which cover several functionalities of products and services. The present work aims to help decision-making in the management of the product portfolio of a family carpentry company, considering four types of product: serial, modular, planned and custom-made furniture. The tools used as methodology are DEIN and AHP. The results indicated that the two tools can be used together, with convergent and aligned results, pointing to the greater viability of the production and sale of serial furniture in the first place, and modulated furniture in sequence, in the furniture market in Juiz de Fora for the final consumer.